A retrospective investigation of women’s experience with breast reconstruction after mastectomy - Ditsch, Nina; Bauerfeind, Ingo; Vodermaier, Andrea; Tripp, Christina; Löhrs, Bettina; Toth, Bettina; Himsl, Isabelle; Graeser, Monika; Harbeck, Nadia; Lenhard, Miriam (Archives of gynecology and obstetrics, 2013)
A diagnosis of breast cancer is often accompanied by the fear of loss of previous body image and attractiveness. Hence, many patients opt for reconstructive surgery. This study evaluated the effects of different types of reconstructive surgery after mastectomy on the functional and psychological adjustment of patients.
Published online: 23 October 2012
Gesehen am 17.12.2020